Legal professional restrictions of medical professionals under the legislation of Ukraine: problems and prospects - Aleksіeіev, O. H.; Anishchenko, M. A.; Алексєєв, Олександр Германович; Аніщенко, Михайло Анатолійович; Алексеев, А. Г.; Анищенко, М. А. (Запорізький державний медичний університет, 2019)
The aim: to conduct a system analysis of the complex of legislative restrictions in the professional activities of medical pro¬fessionals from the standpoint of medical law, define the notion of “legal professional restrictions of medical workers”, identify problems of legal regulation of these legal relations and outline the ways to resolve them. Materials and methods. The research material is a modern regulatory framework. The methods of information retrieval, analysis, systematization and generalization were carried out. Results. In accordance with the innovations of Article 781 of the Fundamentals, from August 1, 2012, medical and pharmaceu¬tical professionals began to be subject to legal restrictions on their professional activities. Simultaneously with the addition of the Fundamentals of the Legislation of Ukraine on Health Protection in Article 781 of the Law of Ukraine, the Code of Ukraine on Administrative Offenses underwent corresponding changes. The introduction of restrictions is quite natural. Having entered into force, these provisions should increase the social responsibility of all participants in a legal relationship, and their main goal is to establish obstacles to possible abuse, create conditions for the independence of professional activity, and guarantee the patient’s right to qualified medical care. Conclusions. Legal professional restrictions of medical professionals represent the limitation of professional rights and du¬ties of medical professionals, established by law in order to ensure public interests, prevent offenses, protect the rights and legitimate interests of medical professionals themselves. Мета роботи – виконати системний аналіз із позицій медичного права комплексу законодавчих обмежень у професійній діяльності медичних працівників, дати визначення поняттю «правові професійні обмеження медичних працівників», виявити проблеми правового регулювання названих правовідносин та окреслити шляхи їх вирішення. Матеріали та методи. Матеріал дослідження – сучасна нормативно-правова база. Використали методи інформаційного пошуку, аналізу, систематизації та узагальнення. Результати. Відповідно до нововведень статті 781 Основ від 1 серпня 2012 року на медичних і фармацевтичних пра¬цівників стали поширюватися визначені законом обмеження при здійсненні ними професійної діяльності. Одночасно з доповненням Основ законодавства України про охорону здоров’я в статті 781 Закону України відповідних змін зазнав і Кодекс України про адміністративні правопорушення. Введення обмежень цілком закономірне. Набравши чинності, такі положення повинні підвищити соціальну відповідальність усіх учасників правовідносин, а їхньою основною метою є встановлення перешкод можливим зловживанням, створення умов для незалежності професійної діяльності, гаран¬тованості прав пацієнта на кваліфіковану медичну допомогу. Висновки. Правові професійні обмеження медичних працівників є лімітуванням професійних прав, обов’язків медичних працівників, що встановлені законодавством для забезпечення публічних інтересів, запобігання правопорушенням, захисту прав і законних інтересів пацієнтів і самих медичних працівників. Цель работы – провести системный анализ с позиций медицинского права комплекса законодательных ограничений в профессиональной деятельности медицинских работников, дать определение понятию «правовые профессиональные ограничения медицинских работников», выявить проблемы правового регулирования указанных правоотношений и очертить пути их разрешения. Материалы и методы. Материал исследования – современная нормативно-правовая база. Использованы методы информационного поиска, анализа, систематизации и обобщения. Результаты. В соответствии с нововведениями статьи 781 Основ с 1 августа 2012 года на медицинских и фармацевти¬ческих работников стали распространяться определенные законом ограничения при осуществлении ими профессио¬нальной деятельности. Одновременно с дополнением Основ законодательства Украины об охране здоровья в статье 781 Закона Украины соответствующих изменений претерпел и Кодекс Украины об административных правонарушениях. Введение ограничений вполне закономерно. Вступив в силу, данные положения должны повысить социальную ответ¬ственность всех участников правоотношения, а их основной целью является установление препятствий возможным злоупотреблениям, создание условий для независимости профессиональной деятельности, гарантированности прав пациента на квалифицированную медицинскую помощь. Выводы. Правовые профессиональные ограничения медицинских работников представляют собой лимитирование профессиональных прав и обязанностей медицинских работников, установленные законодательством для обеспече¬ния публичных интересов, предупреждения правонарушений, защиты прав и законных интересов пациентов и самих медицинских работников.
Правові професійні обмеження медичних працівників згідно з законодавством України: проблеми та перспективи
Правовые профессиональные ограничения медицинских работников по законодательству Украины: проблемы и перспективы
Keywords: professional misconduct; medical law; професійних норм порушення; медичне законодавство; норм нарушения; медицинское законодательство